Ekonomi Kerakyatan dan Koperasi Credit Union (CU): Peran Credit Union dalam Menggerakkan Ekonomi Rakyat di Wilayah Pedesaan - Valentina Keni (Universitas Methodist Indonesia, 2025)
This study examines the role of Credit Unions (CUs) as community-based financial institutions in promoting economic growth among rural communities. Amid challenges such as limited access to capital, low financial literacy, and scarce business opportunities in villages, CUs emerge as a solution to strengthen the economic self-reliance of local residents. Using a descriptive qualitative approach, this research explores the role of CUs in providing financial services such as savings and loans, financial education, and support for micro and small enterprises. The findings indicate that CUs have a positive impact on improving members' economic well-being, fostering a savings culture, and building a fair and sustainable local economic system. Beyond being financial institutions, CUs also serve as tools for social empowerment and symbols of economic solidarity in rural areas. Therefore, strengthening CU institutions and developing cross-sector collaboration—including with government and the private sector—is essential to expanding the reach and effectiveness of CUs in building an inclusive rural economy.